Upaya Penyelesaian Sistem Online Dispute Resolution (ODR) dalam Kasus Penipuan Penjualan Kosmetik melalui Media E-Commerce di Indonesia - Komang Salsa Dila Widiantari (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Fraud in cosmetic buying and selling transactions through e-commerce in Indonesia is increasing along with the growth in the use of digital technology. As a mitigation measure, the Online Dispute Resolution (ODR) system, which is one of the Alternative Dispute Resolution (ADR) dispute resolution techniques, has begun to develop into an efficient alternative solution. This article discusses efforts to apply ODR in dispute resolution of cosmetics sales fraud cases through e-commerce platforms in Indonesia. Apart from Indonesia, the application of ODR is also carried out in the United States. By utilizing ODR mechanisms, consumers can file claims, resolve conflicts, and obtain fair solutions quickly and easily without having to go through conventional court processes. In addition, this article also explores the challenges of ODR implementation in Indonesia, including regulatory constraints and the level of consumer confidence. This research is conducted using a normative juridical approach, which is expected to provide strategic recommendations in strengthening ODR regulations and infrastructure in Indonesia.